2016
DOI: 10.1111/pcn.12454
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and self‐evaluated attention‐deficit hyperactivity disorder traits among Japanese college students

Abstract: Aim Internet addiction (IA), also referred to as Internet use disorder, is a serious problem all over the world, especially in Asian countries. Severe IA in students may be linked to academic failure, attention-deficit hyperactivity disorder (ADHD), and forms of social withdrawal, such as hikikomori. In this study, we performed a survey to investigate the relation between IA and ADHD symptoms among college students. Methods Severity of IA and ADHD traits was assessed by self-report scales. Subjects were 403 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 30 publications
4
62
1
Order By: Relevance
“…We adopted an IAT cut‐off score of 40, and we consider our results to be similar to those of other countries’ university students. Another study from Japan that targeted university students found PIU prevalence to be as high as 63.5% . This is presumably because the study recruited subjects via social networking services (SNS) in a single city, and therefore selection bias may have existed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We adopted an IAT cut‐off score of 40, and we consider our results to be similar to those of other countries’ university students. Another study from Japan that targeted university students found PIU prevalence to be as high as 63.5% . This is presumably because the study recruited subjects via social networking services (SNS) in a single city, and therefore selection bias may have existed.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the IAT was developed about two decades ago under conditions where Internet access was limited, and therefore the cut‐off values of IAT 40 might be inappropriate to define ‘problematic’ Internet use now. As the IAT includes questions regarding dysfunctionality associated with Internet use (such as ‘How often do your job performance or productivity suffer because of the internet?’), we considered IAT to still be usable today, in addition to the fact that many studies to date have used the scale . However, we believe that the invention of a new scale to better fit modern Internet use is required in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations